(3LhGH Ydi GYJQGVGJ EHQGgje Hf eMeO Hf CMeO Hf YR GdOjf GdeDjOi hbOMg aj SjQI ESeGYjds - (3YeGO GdOjf jMji Hf CMeO Hf eMeO Hf UdGM GdTQajs ((3CMeO Hf fGUQ GdSeGhi s)
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO hHYO aEfg GdeGhQO ef GdSjO EHQGgje Hf eMeO Hf CMeO Hf YR GdOjf GdeDjOi eGhQO ef GdbOM ai SjQI ehdGfG ESeGYjd Hf CejQ GdeDefjf QCjJ Cf CPcQbHd GdebUhO TjFkG ef MGd gPG GdWGYf ai GdSjQI s
(3BNQgG (B:s
(3hgPG dGjNai Ydi ef jQjO Sdhc GdEfUGa hjJCed ehGbY GdGehQ HPgf Yf GdCghi hGddg hdi GdJhajb GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbd ef GdLRA GdChd ef GdJfHjgg hGdOdGFd ddefUhQ HGddg GdbGSe Hf Ydis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs